2012
DOI: 10.1017/s1368980012003151
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of plant sterol intake estimated with the Northern Sweden FFQ

Abstract: Objective: To evaluate plant sterol intake estimated with the eighty-four-item Northern Sweden FFQ against repeated 24 h dietary recalls (24-HDR) as the reference method. Design: Randomly recruited participants from the Västerbotten Intervention Programme (VIP) responded to an FFQ (FFQ1). Over the subsequent 12 months, ten repeated 24-HDR were carried out. After this, a second FFQ (FFQ2) was completed. Setting: Västerbotten county, northern Sweden. Subjects: Ninety-six men and ninety-nine women. Results: The P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
0
15
1
Order By: Relevance
“…Total estimated daily intake of energy (excluding energy from alcohol) and nutrients was calculated by weighting reported intake frequencies by food composition provided by the National Food Agency ( https://www.livsmedelsverket.se/en/food-and-content/naringsamnen/livsmedelsdatabasen ). Estimated intake of energy, nutrients, vitamins and minerals was previously validated against repeated 24-h dietary records and biological markers [ 25 – 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Total estimated daily intake of energy (excluding energy from alcohol) and nutrients was calculated by weighting reported intake frequencies by food composition provided by the National Food Agency ( https://www.livsmedelsverket.se/en/food-and-content/naringsamnen/livsmedelsdatabasen ). Estimated intake of energy, nutrients, vitamins and minerals was previously validated against repeated 24-h dietary records and biological markers [ 25 – 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…For other foods, sex- and age-specific average portion sizes as reported in a validation study in a subset of VIP participants using 24-h recall interviews [10] or as reported by the Swedish Food Agency [12] have been used. In addition to the validation study by 24-h recall interviews [10, 13], the FFQ also has been validated by serum biomarkers [14, 15]. …”
Section: Methodsmentioning
confidence: 99%
“…After validation and calibration with 10 repeated 24-h diet recalls, the 84-question FFQ was concluded to have a validity similar to other FFQs used in prospective cohort studies (27). The FFQ has also been evaluated with regard to the ability to estimate plant sterol intake (28). Calculation of nutrient intake from the FFQ has been described elsewhere (29), as have the criteria for incomplete dietary data (27), including missing responses to >10% of the FFQ questions or one or more missing portion size response.…”
Section: Methodsmentioning
confidence: 99%
“…The calibration coefficients were calculated by linear regression of the plant sterol intake estimated with repeated 24 h recalls on the plant sterol intake estimated with the 84-item FFQ (28).…”
Section: Methodsmentioning
confidence: 99%